Oposisi Biner dalam “Lettres de Mon Moulin” Karya Alphonse Daudet - Rifqi Ayu Everina (Lingua Susastra, 2021)
Binary opposition is the most important aspect that can reveal how humans think, how humans produce meaning and understand reality (Culler, 1976). Therefore, the discovery of binary oppositions is useful in providing clues to the workings of human reason. In the context of narrative analysis, binary opposition can reveal how the logic behind a narrative is made. Based on this, this study highlights how the formation of binary opposition contained in the novel "Lettres de Mon Moulin" by Alphonse Daudet uses Lévi Strauss's theory of binary opposition (1955) and structural analysis using Freytag's plot theory (1863). The corpus of the research consists of six stories contained in the novel forming a binary opposition. After doing the analysis, it was found that a pair of words with binary opposition were included in the exclusive category and two pairs of words that were included in the non-exclusive binary opposition category. From these findings, it was found that the author of the novel, Daudet, gave directions on what was good and bad by giving a clear line of separation. This is in line with the context of making stories during the industrial revolution, which mapped the world into two things, namely traditional and modern life.